The role of labor-income risk in household risk-taking? - Sylwia Hubar; Christos Koulovatianos; Jian Li (Goethe University Frankfurt, Center for Financial Studies (CFS), 2020)
In fifteen European countries, China, and the US, stocks and business equity as a share of total household assets are represented by an increasing and convex function of income/wealth. A parsimonious model fitted to the data shows why background labor-income risk can explain much of this risk-taking pattern. Uncontrollable labor-income risk stresses middle-income households more because labor income is a larger fraction of their total lifetime resources compared with the rich. In response, middle-income households reduce (controllable) financial risk. Richer households, having less pressure, can afford more risk-taking. The poor take low risk because they avoid jeopardizing their subsistence consumption.
urn:nbn:de:hebis:30:3-534571
Keywords: G11; D91; D81; D14; D11; E21; 330; background risk; household-portfolio shares; business equity; subsistence consumption; wealth inequality